Combined membrane aeration and membrane filtration for space-efficient nitrogen control in reuse-oriented biological pretreatment - Hsin-Chieh Lin; Ting-Wei Wu; Yu-Tzu Huang; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Enhanced simulations of overland-gully-sewer flow interactions in coupled three-layer dual drainage modeling - Chia-Ho Wang; Hsiang-Lin Yu; Tsang-Jung Chang; Albert S. Chen (Journal of Hydrology, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Glucose-derived carbon-confined cu nanoparticles for selective nitrate reduction to ammonia under acidic conditions and biofouling-resistant wastewater treatment - Tsung-Ying Yang; Ko-Shan Ho; Kan-Yen Hsieh; Yu-Lin Hsiao; Sheng-Ci Jhong; Hsiu-Chung Tu (Journal of Water Process Engineering, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Triarylamine-based epoxy thermosets featuring bright polyelectrochromic energy-storage and energy-saving behaviors - Yu-Jen Shao; Peng-Yi Lin; Hung-Lin Ho; Hsuan-Hsi Pai; William Sun; Yu-Jie Wang; Cha-Wen Chang; Guey-Sheng Liou (Chemical Engineering Journal, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Trans-anethole enhances mesenchymal stem cell derived exosomes function to inhibit H2O2-induced rheumatoid arthritis-like inflammation in HIG-82 synovial cells - Tai-Lung Huang; Yu-Chun Chang; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Kuan-Ho Lin; Tsung-Jung Ho; Chih-Yang Huang (Molecular Biology Reports, 2025)

Energy cycle efficiency of the EU - Tai-Yu Lin; Yung-ho Chiu; Pai-Yun Hsiao (Environment, Development and Sustainability, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Effects of lichen symbiotic bacteria-derived indole-3-acetic acid on the stress responses of an algal–fungal symbiont - Yan-Yu Lin; Han-Chen Ho; Jui-Yu Chou (Brazilian Journal of Microbiology, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Evaluating European countries' progress towards SDGs: Insights from parallel SBM DEA analysis of economic, healthcare, environmental, and educational efficiencies - Tai-Yu Lin; Yung-Ho Chiu; Jia Sheng Lu; Liang-Chun Lu; Hsiu-Fang Chien (Journal of Environmental Management, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Unveiling secondary inorganic PM2.5 pollution in northern Taiwan: The role of aerosol acidity and transformation processes - Ankita Katoch; Chi-Chi Lin; Yu-Chieh Ting; Thi Phuong Thao Ho; Kuan-Ting Liu; Atar Singh Pipal; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

Analyzing the influence of pore structure and vibration on clogging in pervious concrete - Wuguang Lin; Lin Liu; Han Ye; Qifeng Yu; Yoon-Ho Cho (Journal of Cleaner Production, 2025)

An injectable in situ-forming hydrogel with self-activating genipin-chitosan (GpCS) cross-linking and an O2/Ca2+ self-supplying capability for wound healing and rapid hemostasis - Chi Lin; Tzu-Wei Lu; Fang-Yu Hsu; Tzu-Wen Huang; Ming-Hua Ho; Hsien-Tsung Lu; Fwu-Long Mi (Carbohydrate Polymers, 2025)

High performance catalyst CoNP for efficient electrochemical production of hydrogen peroxide - Ko-Shan Ho; Kuan-Ying Hung; Yu-Lin Hsiao; Hsiu-Chung Tu (Journal of Environmental Chemical Engineering, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

The different adsorption-degradation behaviors of SARS-CoV-2 by bioactive chemicals in wastewater: The suppression kinetics and their implications for wastewater-based epidemiology - Mohamed Bayati; Hsin-Yeh Hsieh; Shu-Yu Hsu; Sally Qasim; Chenhui Li; Anthony Belenchia; Jessica Klutts; Sally A. Zemmer; Kristen Sibley; Melissa Reynolds; Elizabeth Semkiw; Hwei-Yiing Johnson; et al. (Science of The Total Environment, 2024)

Retraction Note: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2024)

The joint effect of long-term exposure to multiple air pollutants on non-accidental and cause-specific mortality: A longitudinal cohort study - Xianglin Wei; Kin Fai Ho; Tsung Yu; Changqing Lin; Ly-yun Chang; Dezhong Chen; Tony Tam; Bo Huang; Alexis K.H. Lau; Xiang Qian Lao (Journal of Hazardous Materials, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Numerical seismic performance assessment and fragility analysis for gravity-type wharves considering the influence of soil liquefaction - Yung-Yen Ko; Ho-Hsiung Yang; Chi-Wen Hu; Yan-Jhih Huang; Yu-Ying Lin (Soil Dynamics and Earthquake Engineering, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

Dinaciclib inhibits the growth of acute myeloid leukemia cells through either cell cycle-related or ERK1/STAT3/MYC pathways - Chieh-Lin Jerry Teng; Pang-Ting Cheng; Yu-Chiao Cheng; Jia-Rung Tsai; Mei-Chih Chen; Ho Lin (Toxicology in Vitro, 2024)

Flushing emissions of methane and carbon dioxide from mangrove soils during tidal cycles - Chiao-Wen Lin; Wei-Jen Lin; Chuan-Wen Ho; Yu-Chen Kao; Zhao-Jun Yong; Hsing-Juh Lin (Science of The Total Environment, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Impact assessment of spatial–temporal distribution of riverine dust on air quality using remote sensing data and numerical modeling - Ho-Wen Chen; Chien-Yuan Chen; Guan-Yu Lin (Environmental Science and Pollution Research, 2024)

Single-cell lineage tracing with endogenous markers - Yan Xue; Zezhuo Su; Xinyi Lin; Mun Kay Ho; Ken H. O. Yu (Biophysical Reviews, 2024)
Resolving lineage relationships between cells in an organism provides key insights into the fate of individual cells and drives a fundamental understanding of the process of development and disease. A recent rapid increase in experimental and computational advances for detecting naturally occurring somatic nuclear and mitochondrial mutation at single-cell resolution has expanded lineage tracing from model organisms to humans. This review discusses the advantages and challenges of experimental and computational techniques for cell lineage tracing using somatic mutation as endogenous DNA barcodes to decipher the relationships between cells during development and tumour evolution. We outlook the advantages of spatial clonal evolution analysis and single-cell lineage tracing using endogenous genetic markers.

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Agricultural production efficiency, food consumption, and food waste in the European countries - Tai-Yu Lin; Shih-Yung Chiu; Yung-ho Chiu; Liang-Chun Lu; Kuei-Ying Huang (Environment, Development and Sustainability, 2023)

Stochastic optimal control of mesostructure of supramolecular assemblies using dissipative particle dynamics and dynamic programming with experimental validation - Silabrata Pahari; Yu-Ting Lin; Shuhao Liu; Chi Ho Lee; Mustafa Akbulut; Joseph Sang-Il Kwon (Chemical Engineering Journal, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Construction and demolition waste as a high-efficiency advanced process for organic pollutant degradation in Fenton-like reaction to approach circular economy - Kuan-Ting Lee; Kuan-Yu Ho; Wei-Hsin Chen; Eilhann E. Kwon; Kun-Yi Andrew Lin; Shuenn-Ren Liou (Environmental Pollution, 2023)

Spatial-temporal evaluation of PM2.5 concentration for health risk reduction strategy development in a basin with different weather patterns - Ho-Wen Chen; Chien-Yuan Chen; Teng-Wei Chang; Guan-Yu Lin (Atmospheric Pollution Research, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities - Pei-Sheng Chiu; Shine-Wei Ho; Cheng-Hsuan Huang; Yen-Chun Lee; Yu-Hung Lin (Fishes, 2023)
White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022 to 95,858 eggs per spawning event. Hatching occurred approximately 81 h and 26 min after fertilization at a temperature of 27.0 ± 0.9 °C. Newly hatched larvae had a total length (TL) of 1.91–2.03 mm with 24–26 somites. The larvae transformed into juveniles at 30 days post-hatch. Experiments were conducted at different temperatures (21, 24, 27, 30, and 33 °C) and salinities (18, 24, 30, and 36 ppt) to determine the optimal conditions for larval survival and viability. The results indicate that the most suitable conditions in terms of temperature were in the range of 21–27 °C and 30 ppt for salinity. These findings provide valuable insights for the future development of captive-breeding techniques and the commercial production of other marine ornamental gobies.

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Movement patterns and habitat use of adult giant trevally (Caranx ignobilis) in the South China Sea - Wei-Chuan Chiang; Shian-Jhong Lin; Ker-Yea Soong; Te-Yu Liao; Yu-Yun Chen; Yuan-Shing Ho; Chen-Te Tseng; Michael K. Musyl (Marine Biology, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Flow measurement in open channels using imaging techniques in conjunction with a convolutional neural network - Hao-Che Ho; Yu-Wei Chiu; Ting-Yu Chen; Yen-Cheng Lin (Journal of Hydrology, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

RETRACTED ARTICLE: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2023)

Defect inspection of indoor components in buildings using deep learning object detection and augmented reality - Shun-Hsiang Hsu; Ho-Tin Hung; Yu-Qi Lin; Chia-Ming Chang (Earthquake Engineering and Engineering Vibration, 2023)

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Application of Soil and Water Assessment Tool (SWAT) to evaluate the fates of nitrogenous fertilizer in subtropical mountainous watershed tea farms - Guan-Zhou Lin; Shao-Yiu Hsu; Chia-Chun Ho; Chi-Feng Chen; Jr-Chuan Huang; Tsung-Yu Lee (Environmental Monitoring and Assessment, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

miR-145-5p targets paxillin to attenuate angiotensin II-induced pathological cardiac hypertrophy via downregulation of Rac 1, pJNK, p-c-Jun, NFATc3, ANP and by Sirt-1 upregulation - Kuan-Ho Lin; V. Bharath Kumar; Tamilselvi Shanmugam; Marthandam Asokan Shibu; Ray-Jade Chen; Chia-Hua Kuo; Tsung-Jung Ho; V. Vijaya Padma; Yu-Lan Yeh; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Dynamic analysis of residential and enterprise water supply and leakage efficiencies - Ying Li; Yung-ho Chiu; Yushan Li; Hongyi Cen; Tai-Yu Lin (Environmental Science and Pollution Research, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

EndoPil: A Magnetically Actuated Swallowable Capsule for Weight Management: Development and Trials - Phuoc Thien Phan; Anthony Meng Huat Tiong; Muneaki Miyasaka; Lin Cao; Hung Leng Kaan; Khek Yu Ho; Soo Jay Phee (Annals of Biomedical Engineering, 2021)

Efficiency assessment of coal energy and non-coal energy under bound dynamic DDF DEA - Ying Li; Tai-Yu Lin; Yung-ho Chiu; Hongyi Cen; Yi-Nuo Lin (Environmental Science and Pollution Research, 2021)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Household airborne endotoxin associated with asthma and allergy in elementary school-age children: a case–control study in Kaohsiung, Taiwan - Yu-Chuan Yen; Chun-Yuh Yang; Tsu-Nai Wang; Pei-Chun Yen; Chi-Kung Ho; Kristina D. Mena; Tzu-Chi Lee; Kang-Shin Chen; Yuan-Chung Lin; Pei-Shih Chen (Environmental Science and Pollution Research, 2020)
To evaluate the association between the presence of asthma and allergy, and airborne endotoxin in homes of school-age children in Kaohsiung City, Taiwan, with a case–control study design by matching the age and class exposure. Data collection of home visits included an interviewer-administered questionnaire and air sampling of participants’ homes for endotoxin, bacteria, and fungi, as well as temperature and relative humidity measurements. Endotoxin was detected in all air samples with a median value of 0.67 EU m −3 . In the adjusted logistic regression model, household airborne endotoxin was associated with higher prevalence of asthma and allergy; OR = 4.88 (95% CI 1.16–20.55) for Q3 (between 0.67 and 1.97 EU m −3 ) vs. Q1 (< 0.31 EU m −3 ), with statistical significance. Airborne fungi were associated with higher prevalence of asthma and allergy; OR = 4.47 (95% CI 1.13–17.69) for Q3 (between 314 and 699 CFU m −3 ) vs. Q1 (< 159 CFU m −3 ) in adjusted logistic regression models. Airborne endotoxin and fungi were significantly associated with children’s asthma and allergy.

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

A stochastic multi-objective optimization decision model for energy facility allocation: a case of liquefied petroleum gas station - Ming-Der Yang; Yi-Ping Chen; Chien-Tsung Wang; Ming-Jay Deng; Yu-Hao Lin; Ho-Wen Chen (Clean Technologies and Environmental Policy, 2020)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Slope deformation monitoring in the Jiufenershan landslide using time domain reflectometry technology - Shei-Chen Ho; I-Hui Chen; Yu-Shu Lin; Jun-Yang Chen; Miau-Bin Su (Landslides, 2019)

A new association between goblet worms (Entoprocta) and xeniid corals (Cnidaria) - Vianney Denis; Yu Ting Vicky Lin; Ming Jay Ho (Marine Biodiversity, 2019)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Far infrared promotes wound healing through activation of Notch1 signaling - Yung-Ho Hsu; Yuan-Feng Lin; Cheng-Hsien Chen; Yu-Jhe Chiu; Hui-Wen Chiu (Journal of Molecular Medicine, 2017)

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities - Qi-Lei Chen; Xi-Yu Chen; Lin Zhu; Hu-Biao Chen; Hing-Man Ho; Wing-Ping Yeung; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Expression characterization and promoter activity analysis of the tilapia (Oreochromis niloticus) myosin light chain 3 promoter in skeletal muscle of fish - Yu-Ho Lin; Kuan-Chieh Peng; Chieh-Yu Pan; Zhi-Hong Wen; Jyh-Yih Chen (Transgenic Research, 2014)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

A Review of the Major Penaeid Shrimp EST Studies and the Construction of a Shrimp Transcriptome Database Based on the ESTs from Four Penaeid Shrimp - Jiann-Horng Leu; Shu-Hwa Chen; Yu-Bin Wang; Yen-Chen Chen; Sheng-Yao Su; Chung-Yen Lin; Jan-Ming Ho; Chu-Fang Lo (Marine Biotechnology, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Impact of consistent boundary layer mixing approaches between NAM and CMAQ - Pius Lee; Youhua Tang; Daiwen Kang; Jeff McQueen; Marina Tsidulko; Ho-Chun Huang; Sarah Lu; Mary Hart; Hsin-Mu Lin; Shaocai Yu; Geoff DiMego; Ivanka Stajner; et al. (Environmental Fluid Mechanics, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Pleomorphic extra-renal manifestation of the glomerular podocyte marker podocalyxin in tissues of normal beagle dogs - Wei-Ling Lin; Victor Fei Pang; Chen-Hsuan Liu; Jen-Yau Chen; Kuo-Fang Shen; Yu-Yu Lin; Chun-Ying Yu; Yung-Ho Hsu; Tzuu-Shuh Jou (Histochemistry and Cell Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Aviglycine and propargylglycine inhibit conidial germination and mycelial growth of Fusarium oxysporumf. sp. luffae - Jung-Kang Jin; Douglas O. Adams; Yeong Ko; Chih-Wen Yu; Chin-Ho Lin (Mycopathologia, 2004)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)